Role of Donepezil in Autism: Its Conduciveness in Psychopharmacotherapy - Srivastava, Rohit Kant; Agarwal, Medhavi; Pundhir, Ashish (Case Reports in Psychiatry, 2011)
A woman consulted psychiatric Out-Patient Department (OPD) for her 5-year and 2-month-old son presenting with typical autistic symptoms like social, behavioural, and communicational ineptitudeness. Subsequent treatment with Donepezil resulted in marked improvement in the aforementioned symptomatology. Recent studies in autistic child have shown diminished acetylcholine and nicotinic receptor activity, thus an acetylcholinergic enhancer, Donepezil, likely accounts for improvement in autistic symptoms. Evidently, the case report consolidates Donepezil role as a potentially useful agent in the treatment of cognitive and behavioural symptoms observed in this disorder.